Femtosecond Z-scan measurement of third-order nonlinear optical response of fluorine-doped tin oxide. (1st June 2022) - Zhu, Hao; Huang, Jing; Li, Jie; He, Yuan; Chen, Longlong; Hu, Jianbang; Miao, Lili; Xu, Yanhua; Zhao, Chujun
Abstract: The excitation wavelength dependent nonlinear optical response of fluorine-doped tin oxide (FTO) is systematically studied by the Z-scan technique. The broadband third-order nonlinear optical properties of FTO are verified and a value of nonlinear refractive index coefficient n 2 to be 2.52 × 10 −16 m 2 W −1 is obtained at epsilon-near-zero region. Meanwhile, a large modulation depth and nonlinear absorption coefficient β are estimated about 9.61% and −1.96 × 10 −9 m W −1, respectively. The experimental results indicate that FTO is a promising nonlinear optical material and has great application potential in the field of nonlinear optical devices.